Real Time Simulation of Doubly-Fed Induction Machine IGBT Drive on a PC-Cluster - Shree Ram, Bhagwan; George, Abraham; Ananthi, S. (Asian Journal of Electrical Sciences, 2019)
This paper has presented a device intended to fit in a wind mill based on a Doubly Fed Induction Generator connected to the grid. After a description of this device and its connection procedure, we have established a two-phase mathematical model of the DFIG. In order to control statoric active and reactive power exchanged between the DFIG and the grid, a vector-control strategy has been presented. Simulations have been investigated with two types of regulators: classical proportional-integral and polynomial RST based on pole-placement theory. The synthesis of the RST controller has been detailed. Simulations results have shown that performances are equivalent for the two controllers under ideal conditions (no perturbations and no parameters variations). The RST controller is more efficient when the speed is suddenly changed (which happens frequently in wind energy conversion systems) and is more robust under parameters variations of the DFIG (for example rotoric resistance in our study).